Evaluation of hydrolysed rubber seed meal as a dietary protein source for Nile tilapia Oreochromis niloticus L. (24th October 2016) - Suprayudi, Muhammad Agus; Alim, Sahrul; Fauzi, Ichsan A; Ekasari, Julie; Setiawati, Mia; Junior, Muhammad Zairin; Tacon, Albert G J
Abstract: This study evaluated the use of hydrolysed rubber seed meal as a locally grown alternative feed ingredient to reduce the use of fishmeal within formulated feeds for tilapia. Five experimental diets were prepared by formulating different inclusion levels of hydrolysed rubber seed meal (0%, 25%, 50%, 75% and 100% of plant‐based protein contribution). Dried and defatted rubber seed meal was hydrolysed by adding rumen digesta liquid to the ingredient. For digestibility measurement, chromic oxide was added to each diet as an inert marker. The digestibility trial was conducted over a 14‐day period by collecting faecal matter from the rearing tanks. In addition, a growth trial was conducted over a period of 50 days using four replicates per dietary treatment. In both experiments, all fish were fed three times daily to apparent satiation. At the end of growth trial, the inclusion level of hydrolysed rubber seed meal up to 50% of plant‐based protein contribution did not give any significant difference compared to the control diet in terms of feed efficiency, specific growth rate and protein retention parameters. In the digestibility study, fish fed diets containing hydrolysed rubber seed meal up to a 50% of plant‐based protein inclusion level did not give any significant difference compared to the control diet in terms of protein and dry matter apparent digestibility. Based on the result of this growth and digestibility study, up to a 50% of plant‐based protein contribution of hydrolysed rubber seed meal can be used within formulated tilapia feeds without any adverse effect.